From Russia with Love: A Historical Analysis of Russia Foreign Policy toward North Korea - Fahadayna, Adhi Cahya (Department of International Relations, Universitas Brawijaya, 2023)
The collapse of the Soviet Union and the fall of communism has changed the policy of Russia toward North Korea. However, North Korea has been associated as the closest ally of Russia, even after the collapse of the Soviet Union. This article will explain the transformation of the Russian and Soviet Union relationship using a zero-sum approach. This article shows that Russia prefers to maintain a close relationship with North Korea, with extensive opportunities to improve its economic and security interests within the region of East Asia. Russia will avoid high-risk conflict because it focuses on economic stability. As the closest and critical ally of Russia, North Korea tends to depend on Russia as the sole partner in economic and security. This research will employ a historical approach to unpack the foreign policy dynamics of Russia toward North Korea. The historical analysis is critical to explaining significant factors toward stable relations between two countries.